2022
DOI: 10.1007/s10706-022-02244-0
|View full text |Cite
|
Sign up to set email alerts
|

Resonant Column Tests on Mixtures of Different Sands with Coarse Tyre Rubber Chips

Abstract: The dynamic behaviour of unsaturated sand rubber chips mixtures at various gravimetric contents is evaluated through an experimental study comprising resonant column tests in a fixed-free device. Chips were irregularly shaped with dimensions ranging from 5 to 14 mm. Three types of sand with different gradation have been considered. Relative density amounted to 0.5 for all specimens. Due to the large size of the chips, the diameter of the specimens had to be equal to 100 mm, which in turn required a re-calibrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 25 publications
1
0
0
Order By: Relevance
“…Based on a series of resonant column tests, they 78 showed that the small strain dynamic stiffness (G 𝑜 ) de-79 creases and the initial damping (D 𝑜 ) rises with increas-80 ing rubber content due to the increased number of con-81 tacts between the rubber particles. Similar results were re-82 ported by Banzibaganye and Vrettos (2022) Anastasiadis and proposed strain-dependent 90 shear modulus degradation and damping ratio curves derived 91 from cyclic triaxial and resonant column tests over a wide 92 range of strain amplitudes of SRM and GRM specimens of 93 a wide range of rubber content per mixture weight. Granulated rubber or tire chips have been studied numer-95 ically or experimentally as a lightweight backfill material of 96 retaining walls (Youwai and Bergado, 2004;Hazarika, Ko-97 hama and Sugano, 2008;Tsinaris, Anastasiadis and Pitilakis, 98 2018) and bridge abutments (Argyroudis, Palaiochorinou, 99 Mitoulis and Pitilakis, 2016) or as a drainage layer (Edil 100 and Bosscher, 1994).…”
Section: Introduction 12supporting
confidence: 64%
“…Based on a series of resonant column tests, they 78 showed that the small strain dynamic stiffness (G 𝑜 ) de-79 creases and the initial damping (D 𝑜 ) rises with increas-80 ing rubber content due to the increased number of con-81 tacts between the rubber particles. Similar results were re-82 ported by Banzibaganye and Vrettos (2022) Anastasiadis and proposed strain-dependent 90 shear modulus degradation and damping ratio curves derived 91 from cyclic triaxial and resonant column tests over a wide 92 range of strain amplitudes of SRM and GRM specimens of 93 a wide range of rubber content per mixture weight. Granulated rubber or tire chips have been studied numer-95 ically or experimentally as a lightweight backfill material of 96 retaining walls (Youwai and Bergado, 2004;Hazarika, Ko-97 hama and Sugano, 2008;Tsinaris, Anastasiadis and Pitilakis, 98 2018) and bridge abutments (Argyroudis, Palaiochorinou, 99 Mitoulis and Pitilakis, 2016) or as a drainage layer (Edil 100 and Bosscher, 1994).…”
Section: Introduction 12supporting
confidence: 64%